2014
DOI: 10.1080/13546805.2014.981649
|View full text |Cite
|
Sign up to set email alerts
|

Are there reliable changes in memory and executive functions after cognitive behavioural therapy in patients with obsessive-compulsive disorder?

Abstract: The finding of persistent poor RCFT performances indicates that patients with OCD have impaired visuospatial memory and organisational skills that may be trait-related rather than state-dependent. These impairments may need to be considered in treatment. Our findings underline the importance of correcting for practice effects when investigating changes in cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…OCD can be effectively treated using cognitive behavioral therapy (CBT), including exposure-in vivo and response prevention (ERP), and selective serotonin reuptake inhibitors (SSRI) (24). Some treatment studies using CBT reported effects of treatment on task performance (25)(26)(27)(28)(29), while others did not (30)(31)(32). Some studies reported increased task-related BOLD signal after treatment in the prefrontal, temporal and parietal cortices and putamen (30), whereas others reported decreased taskrelated activation after treatment in the frontal, temporal and parietal lobes, and hippocampal gyrus (25), and decreased insula activation (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCD can be effectively treated using cognitive behavioral therapy (CBT), including exposure-in vivo and response prevention (ERP), and selective serotonin reuptake inhibitors (SSRI) (24). Some treatment studies using CBT reported effects of treatment on task performance (25)(26)(27)(28)(29), while others did not (30)(31)(32). Some studies reported increased task-related BOLD signal after treatment in the prefrontal, temporal and parietal cortices and putamen (30), whereas others reported decreased taskrelated activation after treatment in the frontal, temporal and parietal lobes, and hippocampal gyrus (25), and decreased insula activation (26).…”
Section: Discussionmentioning
confidence: 99%
“…OCD patients have been found to show mild to moderate problems in broad areas of executive function, including response inhibition and processing speed (7), and a recent metaanalysis showed that symptom severity to some extent may affect response time and other neuropsychological measures, though the degree of explained variance is likely small and the majority of studies did not find a significant association (58). There are inconsistent findings of treatment effects on neuropsychological performance, where some studies reported that pre-treatment abnormal task performance (compared with healthy controls) remained after CBT (25,26,31,32), while other studies found improvements after CBT (27)(28)(29)(30). One possible explanation for the inconsistent results in treatment studies may be that previous findings represent a mixture of between-and within-person effects.…”
Section: Discussionmentioning
confidence: 99%
“…Vandborg et al. (2014) observed that patients with OCD performed worse on the RCFT compared to healthy controls both before and after CBT. They concluded that impaired visuospatial memory and organizational skills in patients with OCD could be trait‐related rather than state‐dependent.…”
Section: Discussionmentioning
confidence: 99%
“…[77] Although the difference was not statistically significant, our results indicate a trend wherein patients with OCD who responded to CBGT displayed greater posttreatment improvement in organization strategy on the RCFT and attention and executive function as measured by the TMT than did nonresponders, suggesting that the neuropsychological test performance in these domains could be associated with symptom severity. Vandborg et al (2014) [78] observed that patients with OCD performed worse on the RCFT compared to healthy controls both before and after CBT. They concluded Depression and Anxiety that impaired visuospatial memory and organizational skills in patients with OCD could be trait-related rather than state-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Because different studies highlight the limited scope and quality of the treatments (Jorm et al, 2017), some authors propose specifically treating cognitive deficits in order to improve them and achieve better therapy outcomes. Thus, for example, a recent study found that CBT did not produce changes in memory and executive functions, so these variables were interpreted as traits rather than as states or a consequence of clinical symptoms (Vandborg et al, 2015). In this sense, several authors point out that it is feasible to improve well-established psychological treatments by improving memory and learning through cognitive and educational techniques (Harvey et al, 2014).…”
Section: Evidence In Favor Of Neuropsychological-based Psychothe-rapy For Mental Disorders In Children and Adolescentsmentioning
confidence: 99%